CEO FACULTY TALK SERIES: A SESSION WITH JOHAN MAHMOOD MERICAN ON RAISING GRADUATES’ EMPLOYABILITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 28 November 2016 - Universiti Sains Malaysia (USM) through the USM International Mobility and Career Centre (IMCC) and the School of Social Sciences will organise the ‘CEO Talk Series’, a session featuring the Deputy Director-General of the Economic Planning Unit, Prime Minister’s Department, Johan Mahmood Merican who will share his extensive experience heading various major organisations, including Talent Corporation Malaysia (TalentCorp) with the campus community on Wednesday, 30 November 2016, 2.00 pm at the Dewan Persidangan Universiti (DPU), here.